FAKTOR PENYEBAB KETIDAKLENGKAPAN PENGISIAN FORMULIR PASIEN PULANG BERDASARKAN MIRM 15 DI RS DKT Dr SOETARTO YOGYAKARTA: - - pradnyantara, gusti (Universitas Veteran Bangun Nusantara, 2024)
Background: One of the forms of recording medical record documents is a summary of the patient going home (Discharge Summary). Recording of medical records must be made as complete as possible by a doctor or authorized health worker. However, in reality, it is still common to find forms that are filled out incompletely. From this background, the researcher wants to know what factors cause incompleteness. Objective: To find out what factors cause incompleteness in filling out the patient's discharge form Methods: The research used is descriptive research with a qualitative approach. Results: From the results of interviews conducted, it was found that filling out the forms was following the applicable standard operating procedures, and having carried out socialization regularly, one of the factors that caused the incompleteness was the busyness of the doctor and the burden. The work is so heavy that doctors and nurses forget to fill out the patient's return form Conclusion: filling out the patient's discharge form is following the MIRM 15 standard, and it is expected that the hospital will use this standard. One of the factors that cause incompleteness is the busyness of the doctor and the heavy workload.